Strategy of The Directorate of Narcotics Interdiction of The DJBC To Supervise The International Narcotics Smuggling To Indonesia - Aldila Kun Satriya (Journal Research of Social Science, Economics, and Management, 2023)
The Directorate General of Customs and Excise (DJBC) as the "guard" of the border gate has big challenges in its efforts to supervise international narcotics smuggling into Indonesia. Recently, at DJBC, a special directorate was created to handle narcotics trafficking activities, namely the Narcotics Interdictation Directorate. This study discusses the threats and risks of narcotics trafficking in the context of customs and excise in Indonesia, which makes DJBC need a special directorate of narcotics. The strategy of the Directorate of Narcotics Interdiction of DJBC in an effort to prevent international narcotics smuggling into Indonesia, and the synergy between the Directorate of Narcotics Interdiction of DJBC and the Intelligence Unit of DJBC and other intelligence communities in Indonesia in monitoring and eradicating narcotics smuggling. The research in this thesis uses a qualitative approach. Data collection techniques are through in-depth interviews with internal and external sources of DJBC, observation, and literature review. The researcher uses a number of theories and concepts in this research, namely national security, smuggling, customs and excise, intelligence, strategic intelligence and the intelligence community, and organizational governance. The results of this study indicate a high and worrying threat to narcotics abuse in Indonesia. This threat makes DJBC need a special directorate that focuses on dealing with narcotics smuggling. This special directorate also facilitates the synergy between DGCE and other institutions and between directorates in overseeing the threat of narcotics.